Utilitarianism, institutions, and justice - Bailey, James Wood, 1967- (Oxford University Press, 1997)
This text advances utilitarianism as the basis for a viable public philosophy, rebutting charges that, as moral doctrine, utilitarian thought permits cruel acts, justifies unfair distribution of wealth, and demands too much of moral agents. The author defends utilitarianism using game theory.